Tight budgetary control, business strategy, external environment and firm performance / Muhammad Dahlan, Sofiah Md Auzair and Wan Madznah Wan Ibrahim - Dahlan, Muhammad; Md Auzair, Sofiah; Wan Ibrahim, Wan Madznah (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
Despite the increasing role of non-financial information and continuous criticisms of budgetary processes, budgetary controls are becoming more integrated with firms’ information system to provide cost effective practices and means of tight control. While there has been extensive research on accounting based budgetary controls, little has been done to understand the effect of tight budgetary controls on firms’ performance. This paper reports the findings of a study designed to examine the relationship between tight budgetary control and firms’ performance. Additionally, the effects of two contingent factors, namely, business strategy and external environment are considered.